A scoping review of physical activities for patients with diabetes during COVID-19 pandemic - Kusumaningrum, Niken Safitri Dyan; Febyastuti, Isna Widya (Journal of Holistic Nursing Science, 2021)
Physical activity plays an important role in controlling blood glucose level and reducing the risk of cardiovascular diseases in patients with diabetes. COVID-19 pandemic causes movement restrictions that can affect physical activity in patients with diabetes. This review aimed to describe the physical activity of patients with diabetes during the COVID-19 pandemic. A scoping review of three journal databases including PubMed, SCOPUS, and ScienceDirect was conducted to locate articles that reported physical activities during the COVID-19 pandemic. Articles are selected according to inclusion and exclusion criteria based on the flowchart of the PRISMA-ScR. There were 11 articles that met the inclusion criteria. The results showed that during the COVID-19 pandemic there was a change in the level, type, and place of physical activity in patients with diabetes. The level of physical activity of patients varies with the majority of research showing a decrease in physical activity levels. While the type and place of physical activity turn into physical activity that can be done at home. This review recommended that facilitation should be implemented to increase the motivation and awareness to perform physical activities. Keywords: physical activities; diabetes; health issues; motivation; awareness